2013
DOI: 10.4996/fireecology.0903025
|View full text |Cite
|
Sign up to set email alerts
|

Lepidoptera Pest Species Response to Mid-Summer Fire

Abstract: In the American Midwest, summer fires are infrequent, and there is little information on their impact on ecosystems. After an accidental wildfire in a 20 ha grassland restoration, new growth provided effective substrate for the noctuid species corn earworm, Helicoverpa zea (Boddie), and tobacco budworm, Heliothis virescens (Fabricius). These agricultural pests feed on a number of important crop species and have been implicated in crop losses of up to 50 %. Invertebrate collections were made at 16 days, 45 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, Reilly et al (2016) found that repeated prescribed fire in the southeastern Piedmont changed composition and structure of trees in the midstory but not in the overstory, indicating that foliage-roosting species may be less affected by fire. Many insect taxa, including Lepidoptera, that serve as prey for bats, also benefit from prescribed fire and associated increases in nectar-producing plants (Rudolph 2000) as well as new growth that provides a substrate on which to lay eggs and feed larva (Rudolph 2000;Evans et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, Reilly et al (2016) found that repeated prescribed fire in the southeastern Piedmont changed composition and structure of trees in the midstory but not in the overstory, indicating that foliage-roosting species may be less affected by fire. Many insect taxa, including Lepidoptera, that serve as prey for bats, also benefit from prescribed fire and associated increases in nectar-producing plants (Rudolph 2000) as well as new growth that provides a substrate on which to lay eggs and feed larva (Rudolph 2000;Evans et al 2013).…”
Section: Introductionmentioning
confidence: 99%